1995
DOI: 10.1093/jmedent/32.6.847
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism of Aedes aegypti and Ae. albopictus (Diptera: Culicidae) by Ascogregarina spp. (Apicomplexa: Lecudinidae) in Florida

Abstract: Aedes aegypti (L.) and Ae. albopictus (Skuse) from 40 sites in 17 counties of Florida were surveyed for gregarine parasites during the spring and autumn of 1993 and in July 1994. Larvae collected from containers (mainly tires) were dissected to determine the number of gregarine trophozoites present. Ascogregarina spp. were found at 70% of the sites and occurred as frequently in Ae. aegypti populations as in Ae. albopictus. Within sites, parasite distributions were highly variable and aggregated in host populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 0 publications
3
38
1
Order By: Relevance
“…[20][21][22] It has been proposed that a Gregarine parasite may be mediating competition between the two mosquito species in North America. [23][24][25] However, similar observations have not been reported in Thailand, where Ae. aegypti numbers have remained high even in areas where the two species share larval habitats.…”
Section: Resultsmentioning
confidence: 93%
“…[20][21][22] It has been proposed that a Gregarine parasite may be mediating competition between the two mosquito species in North America. [23][24][25] However, similar observations have not been reported in Thailand, where Ae. aegypti numbers have remained high even in areas where the two species share larval habitats.…”
Section: Resultsmentioning
confidence: 93%
“…Several additional considerations could be made; one possibility is that A. albopictus introduced diseases to the islands that compromise A. aegypti populations (such as Ascogregarina, e.g., Blackmore et al 1995), causing a reduction in their rate of growth. Juliano (1998) found no evidence to support this idea in his Florida competition study, but he did not manipulate the presence or absence of parasites to examine relative susceptibilities, and did not examine dead larvae from his competition experiment, in which some treatment combinations resulted in total larval mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for parasite alteration of a competitive interaction has been shown by Aliabadi and Juliano (2002), who showed a reduced dominance by A. albopictus when competing with native A. triseriatus. The degree of host specificity and pathogenicity by the two species of Ascogregarina involved remains uncertain; some studies indicate that cross-infection between these two mosquitoes and their natural parasites can occur with deleterious effects (Munstermann and Wesson 1990), and others do not (Blackmore et al 1995 found higher prevalence of Ascogregarina spp. among A. aegypti in areas that had not yet been invaded by A. albopictus), but the Ascogregarina-Aedes interactions have still not been thoroughly studied and a number of other parasites, including fungi, flagellates and bacteria could also play a role (Fukuda 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Predators like T. rutilus and C. appendiculata seem to be relatively rare in cemetery vases, tires, and more urban containers in south Florida (Frank 1981;O'Meara et al 1995;personal observation), but there has been relatively little systematic investigation of the question of the potential effects of predators in modifying interspecific competition in these habitats. Although there has been considerable interest in the impact of parasitic protozoa in the genus Ascogregarina on the competitive interaction of A. albopictus and A. aegypti (e.g., Blackmore et al 1995) both observational (Garcia et al 1994) and experimental (Juliano 1998) evidence suggests that Ascogregarina play, at best, a secondary role in determining the outcome of this invasion.…”
Section: Discussionmentioning
confidence: 99%